Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi pada Pra Lansia di Wilayah Kerja UPT Puskesmas Gambut Tahun 2022 - Anisa Puspita Sari; M. Bahrul Ilmi; Ridha Hayati (Jurnal Akademika Baiturrahim Jambi, 2023)
The increase in hypertension cases has always occurred in the last 2 years and is ranked 2nd in the 10 most common diseases in UPT Puskesmas Gambut. The purpose of the study was to determine the factors associated with the incidence of hypertension in the pre-elderly in UPT Puskesmas Gambut Working Area in 2022. This type of research uses quantitative analysis methods with sampling techniques with accidental samples, data collection through questionnaires and research sample data sources of 85 respondents. The results of this study showed that there was a relationship between family history and the incidence of hypertension in the pre-elderly (p-value: 0.007), there was a relationship between sex and the incidence of hypertension in the pre-elderly (p-value: 0.007), there was a relationship of knowledge with the incidence of hypertension in the pre-elderly (p-value 0.003), there was a relationship between the habit of consuming salty foods with the incidence of hypertension in the pre-elderly (p-value: 0.031), there was no relationship between smoking habits and the incidence of hypertension in the pre-elderly (p-value: 1,000), there was an association of physical activity with the incidence of hypertension in the pre-elderly (p-value: 0.004), and no association of BMI with the incidence of hypertension in the pre-elderly (p-value: 0.482). It is recommended that people prevent the incidence of hypertension by carrying out health control and checking blood pressure regularly, as well as doing regular physical activity (sports) activities and doing hobbies that are of interest in order to minimize stress levels. Researchers are then expected to use different research designs such as cohort studies.